مراعاة النبي صتى الله عليه وسلم السياسة الشرعية في تعامله مع مختلف الأحداث والنوازل - سنوسي، امحمد محمد زيد (Jami'at al-Islamiyyah al- 'Alamiyyah Maliziya, 2019)
The focus of this study is to examine the Prophet's methodology on Shari'a policy in dealing with different events and circumstances as seen from his Sunnah. The researcher followed the inductive approach in order to gather and extrapolate the Prophet's Hadiths from the nine Hadith books mentioned on prophetic Shari'a policy. The critical and analytical approaches are also adapted in order to ascertain the validity of the Hadiths pertaining to the sharia. The researcher has reached several results: the most important of which is that the Shari'a policy was set out from clear and legal principles in the Qur'an and Sunnah. The Prophet and his honourable companions considered in their actions and behaviours the requirements of the Shari'a policy that would best safeguard all rights in the community. That the judgments of the legitimate policy in its entirety refer to the rule of minimising embarrassment, protecting the non-guilty and safe guarding the rights of Dhimmi while maintaining the dignity of the ruler.